Pemanfaatan Teknologi Informasi dalam Praktik Keperawatan - Suciari, Ana; Sriyono, Sriyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the use of information technology in nursing practices. The method used is a systematic review with the preferred reporting items for systematic review and meta-analysis (prism). The search uses the Boolean phrase